High‐Entropy Metal Sulfide Nanoparticles Promise High‐Performance Oxygen Evolution Reaction - Cui, Mingjin; Yang, Chunpeng; Li, Boyang; Dong, Qi; Wu, Meiling; Hwang, Sooyeon; Xie, Hua; Wang, Xizheng; Wang, Guofeng; Hu, Liangbing (Advanced energy materials, 2021)
Transition metal sulfides with a multi‐elemental nature represent a class of promising catalysts for oxygen evolution reaction (OER) owing to their good catalytic activity. However, their synthesis remains a challenge due to the thermodynamic immiscibility of the constituent multimetallic elements in a sulfide structure. Herein, for the first time the synthesis of high‐entropy metal sulfide (HEMS, i.e., (CrMnFeCoNi)Sx) solid solution nanoparticles is reported. Computational and X‐ray photoelectron spectroscopy analysis suggest that the (CrMnFeCoNi)Sx exhibits a synergistic effect among metal atoms that leads to desired electronic states to enhance OER activity. The (CrMnFeCoNi)Sx nanoparticles show one of the best activities (low overpotential 295 mV at 100 mA cm−2 in 1 m KOH solution) and good durability (only slight polarization after 10 h by chronopotentiometry) compared with their unary, binary, ternary, and quaternary sulfide counterparts. This work opens up a new synthesis paradigm for high‐entropy compound nanoparticles for highly efficient electrocatalysis applications. High‐entropy metal sulfide (HEMS) nanoparticles are achieved through a pulse thermal decomposition method by overcoming the immiscibility of multiple metallic constituents. Benefiting from synergistic effects and high‐entropy stabilization, nanoscale HEMS greatly promotes oxygen evolution reaction performance. Thus, a new synthesis paradigm for high‐entropy nanomaterials is established for renewable energy conversion and storage applications.